PERANCANGAN SET PRODUK AKSESORIS FESYEN DENGAN PEMANFAATAN SERAT DAUN NANAS - Atmono, Yohanes Firananta Setyo (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Pineapple leaf fiber is a type of fiber that comes from plants which is obtained from the leaves of the pineapple plant. So far, the use of pineapple plants has only been limited to the fruit, while pineapple leaf fiber has not been used relatively much. This research aims to produce a design for a set of feysen accessory products by utilizing pineapple leaf fiber waste. The method used in this research is a qualitative method, namely through material experiments which are then analyzed in more depth. At the data collection stage through literature (previous research journals), research was conducted on pineapple leaf fiber, consumer characteristics, and the potential use of pineapple leaf fiber as raw material for making fashion accessory products, as well as finding out the character and lifestyle of targeted consumers. Then proceed to the prototyping stage to find out the final product physically. Overall, this research shows that pineapple leaf fiber can be a good alternative material for fashion accessory products. This research produces a design output consisting of two sets of fashion accessory product series.